Innovative Molecular Testing Strategies for Adjunctive Investigations in Hemostasis and Thrombosis - Ghorbanpour, Elham; Lillicrap, David (Seminars in Thrombosis and Hemostasis, 2019)
Clinicians and scientists in the fields of hemostasis and thrombosis have been among those first to integrate new molecular strategies for the purpose of enhancing disease diagnosis and treatment. The molecular diagnosis and introduction of gene therapy approaches for hemophilia are obvious examples of this tendency. In this review, the authors summarize information concerning three molecular technologies that have reached various stages of translational potential for their incorporation into the clinical management of disorders of hemostasis. Chromatin conformation assays are now being used to capture structural knowledge of long-range genomic interactions that can alter patterns of gene expression and contribute to quantitative trait pathogenesis. Liquid biopsies in various forms are providing opportunities for early cancer detection, and in the context of tumor-educated platelets, as described here, can also characterize tumor type and the extent of tumor progression. This technology is already being trialed in patients with unprovoked venous thrombosis to assess the potential for occult malignancies. Lastly, advances in single cell transcriptome analysis, provide opportunities to definitively determine molecular events in rare cells, such as antigen-specific regulatory T cells, within the context of heterogeneous cell populations.
Keywords: innovative molecular testing; chromatin conformation testing; liquid biopsies; single cell sequencing